Preventive aspirin use and its association with urinary incontinence in middle-aged and older adult males in the United States: a cross-sectional analysis of NHANES data - Bing-xin Lin; Rui-yao Zhao; Jian-wei Wu; Xiao-ling Chen; Wen-zhong Zheng (The Aging Male)
Background The association between preventive aspirin use and urinary incontinence (UI) among male adults remains poorly understand.Methods In this study, we analyzed data from the National Health and Nutrition Examination Survey (NHANES) collected in the 2011 ∼ 2018 cycle among US male adults, with aspirin use was defined as individuals self-reported use of aspirin. Multi-variable adjusted logistic regression models were used to analysis the association between aspirin use and UI.Results A total of 6844 male participants were evaluated in the study. Compared to participants without aspirin use, the individuals on aspirin with or without coronary heart disease (CVD), respectively, had higher incidences of urinary dysfunction including UI, urgent micturition, and nocturia. In addition, in multivariable logistic adjusted models, the risk of UI (OR = 2.44; 95%CI = 2.10–2.83; P-value = 0.0000) and urgent micturition (OR = 1.57; 95% CI = 1.35–1.83; P-value = 0.0000) in use participants was significantly greater versus the reference those who not taken aspirin.Conclusions The results of this study suggest that men who took aspirin were more likely to report symptoms of UI and urgent micturition. Therefore, reasonable use of aspirin may support the prevent and prevention of UI.